2023
DOI: 10.24976/discov.med.202335174.2
|View full text |Cite
|
Sign up to set email alerts
|

Low-Power Red Laser Treatment for Anisometropic Myopia Control in Children: A Contralateral Comparison Study

Abstract: Background: There are some uncertainties about the effect of low-power red laser treatment on myopia control for anisometropic myopia in children. To evaluate the effect and safety of low-power red laser treatment on refractive development for anisometropic myopia in children, a contralateral comparison study was conducted. Methods: The more myopic eye of child with anisometropic myopia was treated with low-power red laser treatment (LRL group), the other eye received no treatment other than the wearing of sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
2
1
Order By: Relevance
“…Comparisons with previous randomized controlled trials (RCTs) of PBM therapy revealed both similarities and differences. Consistent with prior RCTs ( 14 , 15 , 16 , 17 18 ) significant AL shortening was observed within the first month. However, a notable departure was observed in the timing of maximum AL shortening.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Comparisons with previous randomized controlled trials (RCTs) of PBM therapy revealed both similarities and differences. Consistent with prior RCTs ( 14 , 15 , 16 , 17 18 ) significant AL shortening was observed within the first month. However, a notable departure was observed in the timing of maximum AL shortening.…”
Section: Discussionsupporting
confidence: 88%
“…However, a notable departure was observed in the timing of maximum AL shortening. Unlike previous RCTs ( 4 , 14 , 15 , 16 , 17 18 ), where maximum AL shortening occurred within the first 1–3 months [ 4 ], in this real-world data, the maximum effect occurred at both Month 6 and Month 12, with Month 6 exhibiting particularly pronounced results.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…And neither the choroidal thickness changes nor the cornea curvature could fully explain the negative CARE; That is, AL shortening of myopia recession after weeks of therapy 20 . Experiments either from Jiang Y et al 21 with report the high illumination of 1600lux or from Wang Y et al 22 with report the illumination range of about 1200-1800lux…”
Section: Discussionmentioning
confidence: 99%